Data science at the command line facing the future with time-tested tools - Janssens, Jeroen (O'Reilly Media, 2015)
This hands-on guide demonstrates how the flexibility of the command line can help you become a more efficient and productive data scientist. Even if you're already comfortable processing data with, say, Python or R, you'll greatly improve your data science workflow by also leveraging the power of the command line.